Trauma centers: an underfunded but essential asset to the community - Nasim Ahmed; Joseph L Fracasso (Trauma Surgery & Acute Care Open)
Research indicates that specialized trauma centers, especially those of level I and II designation, can generate revenue if financial support is provided, and most importantly provide better outcomes for an injured patient by reducing length of stay and mortality when compared with treatment at hospitals without trauma center designation.Costs associated with trauma center operation have risen over the past few years in association with growing patient volumes and inflation. Documentation regarding costs for trauma center operations is sparse, and there exists a large variance between reported numbers based on their region. In most cases, the greatest proportion of funds are spent on clinical personnel while the smallest fraction is dedicated to educational and prevention programs. Studies confirm that as a product of these rising costs and a lack of state and federal funding that trauma centers remain uniquely financially vulnerable.Multiple strategies have been implemented to mitigate these costs but have proven insufficient. Legislations providing patients with expanded access to healthcare such as the Affordable Healthcare Act have failed to deliver on their intended purposes, and managed care organizations have moved to protect their own interest at the expense of trauma patient mortality. In lieu of concerted federal support, states and municipalities have explored solutions to support trauma centers such as small fees added to fines or encouraging charitable donations, although these programs have not seen ubiquitous implementation. Most trauma centers have begun incorporating activation costs to recoup losses from their low reimbursement rate, but these have continued to inflate, and pose a growing burden on vulnerable patients.Lack of funding from external sources such as state or federal appropriations poses a tangible threat to trauma centers for closure, and with multiple trauma centers acting as critical pillars of healthcare infrastructure for disadvantaged communities as well as the impact of this lack of funding being so broad and systemic, multiple ‘trauma deserts’ may emerge, leaving communities—especially disadvantaged communities which rely on the safety-net function of many high designation trauma centers—deprived of an essential treatment resource and increasing annual mortalities that could have otherwise been averted.